2021
DOI: 10.1093/cid/ciab932
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Vaccine-Breakthrough Infections Requiring Hospitalization in Mayo Clinic Florida Through August 2021

Abstract: We characterized coronavirus disease 2019 (COVID-19) breakthrough cases admitted to a single center in Florida. With the emergence of delta variant, an increased number of hospitalizations was seen due to breakthrough infections. These patients were older and more likely to have comorbidities. Preventive measures should be maintained even after vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 9 publications
(11 reference statements)
4
33
0
1
Order By: Relevance
“…The clinical and baseline characteristics of our cohort are similar to those of the other two groups of patients hospitalized due to breakthrough COVID-19 (Bosch et al, 2021;Brosh-Nissimov et al, 2021). Compared to unvaccinated COVID-19 admissions, those patients appear to be older, are more likely to be immunosuppressed, and have more comorbidities (Alimohamadi et al, 2021;Andrés et al, 2021;Berenguer et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…The clinical and baseline characteristics of our cohort are similar to those of the other two groups of patients hospitalized due to breakthrough COVID-19 (Bosch et al, 2021;Brosh-Nissimov et al, 2021). Compared to unvaccinated COVID-19 admissions, those patients appear to be older, are more likely to be immunosuppressed, and have more comorbidities (Alimohamadi et al, 2021;Andrés et al, 2021;Berenguer et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…First, the study was a non-controlled observational study based on real-life data obtained from pandemic surveillance activities, aimed not to establish vaccine efficacy compared to a matched unvaccinated control group, but to report a virological characterisation of those patients reported with SARS-CoV-2 infection despite being vaccinated. Therefore, our observation should be replicated and extended on larger cohorts established ad hoc, also including other vaccine formulations as differences in incidence rates of breakthrough infections were observed in previous real-life studies (21,26,27). No follow-up samples were available for the post-vaccination infected individuals so that it was not possible to monitor viral loads dynamics and the shedding.…”
Section: Discussionmentioning
confidence: 77%
“…Severe disease was significantly less frequent in patients infected after a full vaccination course as compared to the patients who acquired the infection after a single dose, supporting the importance of the full vaccination schedule in naïve individuals. Those patients with severe symptoms presented pre-existing co-morbidities (i.e., cardiovascular chronic diseases, diabetes, obesity, renal affections, and neurological disorders) and those aged over 80, which represent still relevant risk factors for disease severity and are prognostic for a negative outcome (3,(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies and a meta-analysis assessing the impact of primary vaccination observed a ≃ 10% reduction in vaccine efficacy against asymptomatic and symptomatic infections with delta VOC, but no reduction of vaccine efficacy against severe forms 2,17 . Some authors have noted that the higher incidence of infections with this VOC may also be due to the fact that when delta became predominant, those infected had received their primary vaccination 4 to 10 months before, meaning that the infection may have been related to the waning of the level of vaccine-induced antibodies 18 .…”
Section: Discussionmentioning
confidence: 99%